A Study on the Cultural Interaction Characteristics of New Generation Migrant Workers Under Symbolic Interaction Theory (Asian Journal of Social Science Studies, 2022)
The term migrant workers was first proposed by researcher Wang Chunguang in 2001 in response to the social phenomenon of rural migrant population working in cities and the social problems arising from it. The emergence of migrant workers is a product of the differences in household registration, labor and employment, health insurance and education systems and the unbalanced and insufficient development in a specific historical period of society and in the stage of urban and rural development. Along with the continuous development of urbanization, a new generation of migrant workers has emerged. In terms of emotional identity, cultural level, career planning, and demand structure, the new generation of migrant workers shows a different posture from the past. To address this phenomenon, this paper takes symbolic interaction theory as the theoretical guide, observes the psychological and emotional structure of the new generation of migrant workers in the current society, and theoretically interprets the content and characteristics of the cultural products of the new generation of migrant workers in the current online platform community.